CBCT-based evaluation of bone microarchitecture in fibro osseous lesions using image analysis - A retrospective radiographic study - S Jayachandran; M Archana (Wolters Kluwer Medknow Publications, 2023)
Background: Cone-beam computed tomography (CBCT) systems are frequently used to image bones for research purposes to investigate trabecular and cortical changes in bone disorders. A unique technique that may be used for the early diagnosis of bone lesions is fractal dimension (FD) analysis and bone architecture analysis using CBCT scans. Aim: To assess and compare the changes in trabecular bone architecture in fibro-osseous lesions by bone image analysis and FD analysis in CBCT scans of fibro-osseous lesions. Materials and Methods: This retrospective analysis included the CBCT scans of 25 patients from archival records of the Department of Oral Medicine and Radiology. As per specific exclusion and inclusion criteria, the radiographs were chosen. To establish a noninvasive assessment of the bone structure, CBCT scans were subjected to bone architecture analysis and FD analysis using box-counting (with ImageJ software). Results and Conclusions: The FD values and bone parameter values on the affected and the normal side will be recorded and analyzed using SPSS version 22. There was a statistically significant difference in the FD values between the normal and abnormal sides in all fibro-osseous lesions. Five parameters in fibrous dysplasia showed a significant statistical difference in comparison to the normal and abnormal sides. It can be concluded that FD analysis provides a novel technique for the early detection of fibro-osseous lesions.